1999
DOI: 10.1071/bt97054
|View full text |Cite
|
Sign up to set email alerts
|

The weed invasion in Tasmania since 1970

Abstract: Tasmanian Herbarium (HO) collections are shown to provide temporal and distributional data to monitor weed introductions into the State flora during the last 25 years. Information obtained from herbarium collections, the botanical literature, and anecdotal sources indicates that since 1970, 159 new plant taxa have been recorded as naturalised in Tasmania, bringing to a total over 740 weed species recorded from the State. Most of these species are from the families Poaceae (15.1%), Fabaceae (10.1%), Asteraceae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 0 publications
0
22
0
1
Order By: Relevance
“…Compiling alien species for a given country has proved to be a useful approach to understanding plant invasion patterns (Rozefelds et al 1999;Stadler et al 2000;Silva and Smith 2004;Khuroo et al 2007) and is the first step towards developing a management strategy for invasive species. Because we focused on invasive species, our species list certainly represents only a fraction of all naturalized alien plants within China's territories.…”
Section: Available Data and Species Numbersmentioning
confidence: 99%
See 1 more Smart Citation
“…Compiling alien species for a given country has proved to be a useful approach to understanding plant invasion patterns (Rozefelds et al 1999;Stadler et al 2000;Silva and Smith 2004;Khuroo et al 2007) and is the first step towards developing a management strategy for invasive species. Because we focused on invasive species, our species list certainly represents only a fraction of all naturalized alien plants within China's territories.…”
Section: Available Data and Species Numbersmentioning
confidence: 99%
“…The most comprehensive study for an east Asian region is probably that for Taiwan (Wu et al 2004a). Compiling alien floras and analyzing patterns of floristic status, biological attributes, and geographical distribution has proved to be a useful approach to understanding alien species richness in various regions (Rozefelds et al 1999;Stadler et al 2000;Pyšek et al 2004;Pyšek and Richardson 2006), and such datasets represent the necessary baseline information upon which management strategies can be built.…”
Section: Introductionmentioning
confidence: 99%
“…Rozefelds & McKenzie's (1999) appraisal of Spicer's publications indicates that by the 1870s, 104 alien plants had become naturalised in Tasmania. A review of more recent statistics of alien invasions in Tasmania was cqmpiled by Rozefelds et al (1999). This research showed that between 1971 and 1995, 159 plant taxa had been recorded as naturalised, bringing the total number to over 740 naturalised taxa.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the literature pertaining to naturalised plant incursions in Tasmania has been summarised by Rozefelds et al (1999) and Rozefelds & McKenzie (1999). Although outdated, particularly with respect to the alien flora, The Student's Flora of Tasmania (Curtis 1963(Curtis , 1967Curtis & Morris 1975, 1994 remains the most comprehensive account of the naturalised plants in Tasmania.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation